LEARNING FROM HOME BASED ON DIGITAL MEDIA AS A REPRESENTATION OF PEDAGOGIC TRANSFORMATION IN THE MILLENNIUM - Ogy Agiustora; Wahendra Wahendra; Kukuh Gotriansyah; Triaji Prasetio (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: Education develops along with the development of science, the development of the times and the development of the idea of educating itself. The science of education or pedagogy is the science that examines how educators guide students, and know about the tasks and goals of educators in educating students. Research methods: In this study the descriptive analytical method of phenomena was used to study an object in the context of pedagogic, media, student and teacher,conditions, systems of thought, and events at the present time. The approach method is a case study to reveal and describe the phenomenon of the subject and object of research on learning from home based on digital media as a representation of pedagogic transformation in the millennium. Findings: Efforts to transform education in the digital era of schools must be able to understand the characteristics of the millennial generation and generation Z to determine an effective educational strategy. The character of today's generation who are familiar with technology requires schools and teachers to utilize digital media as learning tools. The challenge for educators in educational transformation is how teachers are able to create digital media content as creative learning media, and are able to control and curate information for their students. Implications: Eliminating the face-to-face teaching and learning process for a while inevitably students adapt to the current situation and conditions. learning from home (LFH) is the right of every student to get learning education even though it has to be done from home (online) during this pandemic. Understanding the purpose of learning done from home must be instilled in students first. Students must really understand why they have to study from home for a long time. Circular issued by the Ministry of Education and Culture (Kemendikbud) No 15 of 2020 concerning guidelines for learning from home during the emergency period of the spread of Covid 19. The government's consideration of implementing learning from home looks at several aspects, one of which is for health and safety in the world of education both from the school and from the students themselves. We should appreciate the government's steps, one of which is breaking the chain of the corona virus in the world of education.